SPECIES RICHNESS AND INDICES OF ABUNDANCE OF MEDIUM-SIZED MAMMALS IN ANDEAN FOREST AND REFORESTATIONS WITH ANDEAN ALDER: A PRELIMINARY ANALYSIS - SÁNCHEZ FRANCISCO; SÁNCHEZ-PALOMINO PEDRO; CADENA ALBERTO (Caldasia)
We studied the species richness and two indices of abundance of medium-sized mammals in areas with Andean forest and Andean alder (Alnus acuminata) reforestations in a reserve at the Central Andes of Colombia. Since reforested areas have a less complex habitat structure and lower plant diversity than native forests, we predicted that they have lower richness of mammals than areas with Andean forest. We obtained the indices of abundance from direct contacts in transects and from the use of track stations. Our results suggest that, indeed, areas with Andean forest had a higher richness of mammals than reforestations, but this pattern may be modified by anthropogenic factors. We found no differences between the indices of abundance of the squirrel, Sciurus granatensis, in the two forest types. In contrast, the coatis were recorded more frequently in the reforestations than in areas with Andean forest at the reserve.